2021
DOI: 10.3390/foods10092136
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Composition, Antibacterial Activity, and Antioxidant Properties of the Artocarpus altilis Fruits to Promote Their Consumption in the Comoros Islands as Potential Health-Promoting Food or a Source of Bioactive Molecules for the Food Industry

Abstract: The present study aimed to evaluate the health-promoting potential of breadfruit (Artocarpus altilis (Parkinson) Fosberg, Moraceae family), a traditional Comorian food, considering the sample variability according to geographic localisation. Moreover, the main aims of this research were also to promote its consumption in the Comoros Islands as potential health-promoting food and evaluate it as a source of bioactive molecules for the food industry thanks to its antioxidant and antibacterial properties. Investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 61 publications
0
3
0
1
Order By: Relevance
“…Penelitian aktivitas antioksidan dengan metode FRAP pada daun sukun juga diteliti oleh (Soifoini et al, 2021) dimana daun sukun diambil di daerah Grand Comore. Penelitian tersebut menggunakan teknik maserasi dengan 3 pelarut yaitu metanol, air dan HCl dengan rasio 95:4,7:0,3 (v/v/v).…”
Section: Hasil Uji Aktivitas Antioksidan Dengan Metode Frapunclassified
“…Penelitian aktivitas antioksidan dengan metode FRAP pada daun sukun juga diteliti oleh (Soifoini et al, 2021) dimana daun sukun diambil di daerah Grand Comore. Penelitian tersebut menggunakan teknik maserasi dengan 3 pelarut yaitu metanol, air dan HCl dengan rasio 95:4,7:0,3 (v/v/v).…”
Section: Hasil Uji Aktivitas Antioksidan Dengan Metode Frapunclassified
“…Handa et al (88) found that many of breadfruit's phytochemicals confer beneficial biological activity such as anti-bacterial activity, platelet aggregation, anti-fungal properties, anti-tumor agents, and inhibition of leukemia cells. Cinnamic acids and chlorogenic acid were the main phytochemicals found in breadfruit pulp (89,90). Cinnamic acid undergoes rapid metabolism and have shown low bioavailability in the human body making the actualization of therapeutical effects difficult (91).…”
Section: Meat Analogsmentioning
confidence: 99%
“…Alkaloid with antiobesity property isolated, synephrine from Citrus aurantium , nuciferine from Nelumbo nucifera , piperine and piperlongumine from Piper nigrum . Green coffee reduced body fat by decreasing the absorption of glucose [ 136 138 ]. Phenols are an important phytochemical and reduce the risk of obesity such as p-hydroxybenzoic, cinnamic acid, ferulic acid, caffeic acid, p-coumaric, and cinnamic acid [ 139 141 ].…”
Section: Therapeutic Application Of Phytochemicals In Obesitymentioning
confidence: 99%